Efficacy of Insecticide and Bioinsecticide Ground Sprays to Control Metisa plana Walker (Lepidoptera: Psychidae) in Oil Palm Plantations, Malaysia - Hasber Salim; Che Salmah Md. Raw; Abu Hassan Ahmad; Salman Abdo Al-Shami (Tropical Life Sciences Research, 2015)
The effectiveness of the synthetic insecticides trichlorfon, lambda-cyhalothrin, cypermethrin emulsion concentrated (EC) and cypermethrin emulsion water based (EW) and a bio-insecticide, Bacillus thuringiensis subsp. kurstaki (Btk), was evaluated at 3, 7, 14 and 30 days after treatment (DAT) for the control of Metisa plana larvae in an oil palm (Elaeis guineensis) plantation in Malaysia. Although all synthetic insecticides effectively reduced the larval population of M. plana, trichlorfon, lambda-cyhalothrin and cypermethrin EC were the fastest-acting. The larval population dropped below the economic threshold level (ETL) 30 days after a single application of the synthetic insecticides. Application of Btk, however, gave poor results, with the larval population remaining above the ETL post treatment. In terms of operational productivity, ground spraying using power spray equipment was time-consuming and resulted in poor coverage. Power spraying may not be appropriate for controlling M. plana infestations in large fields. Using a power sprayer, one man could cover 2–3 ha per day. Hence, power spraying is recommended during outbreaks of infestation in areas smaller than 50 ha. Keberkesanan racun serangga sintetik trichlorfon, lambda-cyhalothrin, cypermethrin emulsion concentrated (EC) dan cypermethrin emulsion water based (EW) serta racun serangga biologi, Bacillus thuringiensis subsp. kurstaki (Btk), telah dinilai pada 3, 7, 14 dan 30 hari selepas rawatan (DAT) bagi mengawal larva Metisa plana pada kelapa sawit (Elaeis guineensis) di Malaysia. Walaupun semua rawatan racun serangga sintetik berkesan mengurangkan populasi larva M. plana, trichlorfon, lambda-cyhalothrin dan cypermethrin EC adalah yang paling cepat bertindak. Populasi larva jatuh di bawah paras ambang ekonomi (ETL) 30 hari selepas satu pusingan rawatan bagi racun serangga sintetik. Penggunaan Btk, bagaimanapun, memberi keputusan yang kurang berkesan dengan populasi larva berada di atas ETL selepas rawatan. Dari segi produktiviti, semburan paras tanah menggunakan alatan power sprayer kurang produktif dan mempunyai luas litupan yang rendah. Teknik semburan paras tanah menggunakan peralatan power sprayer mungkin tidak sesuai untuk mengawal serangan M. plana di kawasan yang luas. Menggunakan teknik aplikasi ini seorang pekerja hanya mampu menyiapkan semburan sebanyak 2–3 hektar sehari. Oleh itu, teknik semburan paras tanah adalah disyorkan mengawal serangan perosak di kawasan yang kecil dari 50 hektar.